2021
DOI: 10.3390/systems9030055
|View full text |Cite
|
Sign up to set email alerts
|

Startup Investment Decision Support: Application of Venture Capital Scorecards Using Machine Learning Approaches

Abstract: This research aims to explore which kinds of metrics are more valuable in making investment decisions for a venture capital firm using machine learning methods. We measure the fit of developed companies to a venture capital firm’s investment thesis with a balanced scorecard based on quantitative and qualitative characteristics of the companies. Collaborating with the management team of Rose Street Capital (RSC), we explore the most influential factors of their balanced scorecard using their retrospective inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Additionally, deep learning models have been used in the context of investment decision-making. For example, research by Bai and Zhao Bai & Zhao (2021) applies a venture capital scorecard using a machine learning approach to support startup investment decisions [48]. Additionally, research by Martinez et al (2020) showed that deep reinforcement learning can be used for early adaptive classification of temporal sequences, where agents learn to make adaptive decisions between classifying incomplete sequences now or delaying their predictions to collect more data [49].…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, deep learning models have been used in the context of investment decision-making. For example, research by Bai and Zhao Bai & Zhao (2021) applies a venture capital scorecard using a machine learning approach to support startup investment decisions [48]. Additionally, research by Martinez et al (2020) showed that deep reinforcement learning can be used for early adaptive classification of temporal sequences, where agents learn to make adaptive decisions between classifying incomplete sequences now or delaying their predictions to collect more data [49].…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, venture capital firms require new technologies to extract factors that influence the quality of their investment decisions. They employ machine learning algorithms to determine that the most important factors to consider when investing in a startup are strategic planning and team management [74].…”
Section: ) Demand For Intelligent Decision-makingmentioning
confidence: 99%
“…In this SAFLSTM, the SAF is used instead of the sigmoid activation function for enhancing the classification. Swish is motivated by the utilization of the sigmoid function for gate control in LSTM and highway networks where this SAF is expressed in the equation (11) Swish (𝑥) = 𝑥. 𝑆igmoid (𝑥). Further, the derivative expression of the swish is expressed by (12) Swish ′ (𝑥) = 𝑒 𝑥 (1+𝑒 𝑥 +𝑥) (1+𝑒 𝑥 ) 2 .…”
Section: Classification Using Saflstmmentioning
confidence: 99%
“…Hence, the success and failure evaluation of startups become crucial for both forthcoming and well-established entrepreneurs, and stakeholders [10]. The startup evaluation is highly subjective and preliminary-stage startups are correspondingly unpredictable as there is less amount of historical data [11]. The survival prediction of the new venture is difficult because the output is mainly based on the environmental improvements and certain complexity of each venture [12].…”
Section: Introductionmentioning
confidence: 99%